1979
DOI: 10.1161/01.hyp.1.5.498
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypothalamic stimulation in awake rats fails to induce hypertension.

Abstract: SUMMARY Daily electrical stimulation of tbe posterior hypothalamus for 12 weeks in awake rats caused persistent cardioacceleration but barely increased systolic pressure. Subsequent postmortem examination showed extensive fibrosis at sites of electrode implantation in both stimulated and unstimulated rats. Because Folkow and Rubinstein had succeeded in elevating blood pressure progressively by stimulating the "hypothalamic defence area," chronic stimulation was repeated following their stereotaxic coordinates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 19 publications
(12 reference statements)
1
2
0
Order By: Relevance
“…Behavioral and cardiovascular responses elicited upon subsequent electrical stimulation of the ventromedial hypothalamus were qualitatively similar to those described previously for the posterior 27 and anterior 20 hypothalamus. As current strengths used for stimulation were made stronger, behavioral effects also became progressively more pronounced, and four phases could be identified.…”
Section: Behavioral and Cardiovascular Effects Of Hypothalamic Stimulsupporting
confidence: 75%
“…Behavioral and cardiovascular responses elicited upon subsequent electrical stimulation of the ventromedial hypothalamus were qualitatively similar to those described previously for the posterior 27 and anterior 20 hypothalamus. As current strengths used for stimulation were made stronger, behavioral effects also became progressively more pronounced, and four phases could be identified.…”
Section: Behavioral and Cardiovascular Effects Of Hypothalamic Stimulsupporting
confidence: 75%
“…Increases in CBF-TR were noted in the PH, DMH, and VMH. Past work has shown that stimulation or disinhibition of the PH and DMH increases blood pressure, heart, and respiratory rate and escape-defense behavior (Bunag et al, 1975;Bunag and Riley, 1979;Shekhar et al, 1990;Samuels et al, 2004). With projections to midline thalamic nuclei and brainstem cardiovascular centers (Vertes et al, 1995;Vertes and Crane, 1996), the PH has been proposed to be in a position to receive converging sensory and limbic input and, thus, alter the levels of cerebral activation, as well as cardiovascular tone.…”
Section: Hypothalamusmentioning
confidence: 99%
“…ously described, 13 current thresholds were determined in each rat by starting stimulation with 50 fiA and progressively increasing current strength by 20 fiA increments until a 2 mm Hg increase in mean pressure occurred.…”
Section: Group 1 Terminal Experiments: Effects Of Bilateral Electrolymentioning
confidence: 99%